Impact of universities in a flat hierarchy: Do degrees from top universities lead to a higher wage? - Jakob Schwerter (ZBW - Leibniz Information Centre for Economics, 2020)
The literature shows a wage premium for graduates from high quality, elite, or more selective universities. The results, however, exist for countries with a clear hierarchy of top universities, such as the US, England, and Australia. I evaluate if such an effect also exists in Germany, a country in which universities are top-performing in some but not all fields, and the general differences between universities are smaller compared to, e.g., the USA. I use the University Ranking of the Quacquarelli Symonds and a revealed preference and acceptance ranking to measure the quality of a university. Both rankings show a wage premium in IV regression in-between five and 13 percent. This effect is specially prevalent for women.
Keywords: I23; I24; I26; J31; 330; wage premium; ranking; revealed preferences; Germany